PENERAPAN PROGRAM PENDIDIKAN INKLUSI DI SDN 1 SANGKAWANA LOMBOK TENGAH - Deni Sutisna; Dyah Indraswati; Nursaptini Nursaptini; Setiani Novitasari; Muhammad Sobri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2020)
This study aims to examine implementation of the Inclusive program in schools, specifically SDN 1 Sangkawana. The study was conducted with a descriptive qualitative approach with Observation techniques, interviews, documentation. The key informants in this study were the principal, the coordinator of the inclusive school and teachers of grades 1, 2 and 3. The data validity technique used triangulation of sources. The results showed that the application of the inclusive education program at SDN 1 Sangkawana was divided into 2 stages, namely the preparatory stage and the implementation stage. During the preparatory phase at the beginning of the new school year, the work program for SDN 1 Sangkawana refers to the program of the Minister of National Education Republic of Indonesia Number 70 of 2009 concerning inclusive education. At the application stage, SDN 1 Sangkawana touched on several aspects, namely curriculum, teaching staff, infrastructure. Teaching and learning processes that are integrated between students with special needs and regular students force schools to adjust the curriculum to facilitate students with special needs without leaving aside regular students. Therefore some changes were made in the syllabus and lesson plans, especially in the indicators of competency achievement, learning objectives, learning materials and learning evaluation. For educators, the school is facilitated by the Ministry of Education and Culture formed by cooperating with the Australian government with the INNOVATION program so that teachers and schools get guidance, direction and training to handle students with special needs integrated in the regular classrooms. For inclusive education facilities and infrastructure, SDN 1 Sangkawana is still lacking, so it still needs to be developed and organized to support the successful implementation of an inclusive education program.